Action research and intervention research in the French landscape of organizational research. Issue 4 (7th October 2014) - Stokes, Peter; Davoine, Eric; Oiry, Ewan; Savall, Henri; Zardet, Véronique
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to present a concise history of the main action research (AR) contribution in France. The authors discuss the role of AR in the organizational research field in general and compare it with intervention research (IR) and presented Institute of Socio-Economy of Enterprises and Organizations's specific contributions and its presence on the international stage through review publications and wider works. Design/methodology/approach – A narrative approach was used to analyze this history. Findings – AR is considered as a research family. The authors define and compare AR with other qualitative methods. They analyze AR and IR principles, which include interaction with practitioners, negotiation with them, focusing in the third part on the case of ISEOR research team. Social implications – AR and IR permit to bridge the gap between researchers and practitioners, to develop useful research. At the same time, they permit to develop new researchers' competencies and to fund research, in a context of reduced public research funds. Originality/value – This article permits to understand the reality of what is and how to develop an IR, and the difficulties for researchers to insert them in the academic community, although France seems to be more permissive than others' contexts. It permits also to better know the French IR and AR research in management.